Molecular Mechanisms Related to Oxidative Stress in Retinitis Pigmentosa - Carla Enrica Gallenga; Maria Lonardi; Sofia Pacetti; Sara Silvia Violanti; Paolo Tassinari; Francesco Di Virgilio; Mauro Tognon; Paolo Perri (MDPI AG, 2021)
Retinitis pigmentosa (RP) is an inherited retinopathy. Nevertheless, non-genetic biological factors play a central role in its pathogenesis and progression, including inflammation, autophagy and oxidative stress. The retina is particularly affected by oxidative stress due to its high metabolic rate and oxygen consumption as well as photosensitizer molecules inside the photoreceptors being constantly subjected to light/oxidative stress, which induces accumulation of ROS in RPE, caused by damaged photoreceptor's daily recycling. Oxidative DNA damage is a key regulator of microglial activation and photoreceptor degeneration in RP, as well as mutations in endogenous antioxidant pathways involved in DNA repair, oxidative stress protection and activation of antioxidant enzymes (MUTYH, CERKL and GLO1 genes, respectively). Moreover, exposure to oxidative stress alters the expression of micro-RNA (miRNAs) and of long non-codingRNA (lncRNAs), which might be implicated in RP etiopathogenesis and progression, modifying gene expression and cellular response to oxidative stress. The upregulation of the P2X7 receptor (P2X7R) also seems to be involved, causing pro-inflammatory cytokines and ROS release by macrophages and microglia, contributing to neuroinflammatory and neurodegenerative progression in RP. The multiple pathways analysed demonstrate that oxidative microglial activation may trigger the vicious cycle of non-resolved neuroinflammation and degeneration, suggesting that microglia may be a key therapy target of oxidative stress in RP.